2009
DOI: 10.3748/wjg.15.5442
|View full text |Cite
|
Sign up to set email alerts
|

Stable knockdown of heparanase expression in gastriccancer cells in vitro

Abstract: AIM:To develop short hairpin RNA (shRNA) against heparanase, and to determine its effects on heparanase expression and the malignant characteristics of gastric cancer cells. METHODS:Heparanase-specific shRNA was constructed and transferred into cultured the gastric cancer cell line SGC-7901. Stable subclonal cells were screened by G418 selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
1
7
2
Order By: Relevance
“…These apparently contradictory results may be reconciled by the observation that an increased number of heparanase‐positive tumour cells were inversely correlated with a four‐fold decrease in tumour cell proliferation. A common finding by others is that heparanase can enzymatically influence cell migration and invasiveness, but not proliferation; 41–43 for example, in a stable heparanase knockdown model in gastric cancer, migration and invasiveness were reduced, but not tumour cell proliferation 44 . Further studies also clearly showed that heparanase‐expressing cells were able to activate neighbouring tumour and non‐tumour cells (such as endothelial cells), with subsequent improved cell migration and invasiveness, but no notable increase in proliferation 45 .…”
Section: Discussionmentioning
confidence: 95%
“…These apparently contradictory results may be reconciled by the observation that an increased number of heparanase‐positive tumour cells were inversely correlated with a four‐fold decrease in tumour cell proliferation. A common finding by others is that heparanase can enzymatically influence cell migration and invasiveness, but not proliferation; 41–43 for example, in a stable heparanase knockdown model in gastric cancer, migration and invasiveness were reduced, but not tumour cell proliferation 44 . Further studies also clearly showed that heparanase‐expressing cells were able to activate neighbouring tumour and non‐tumour cells (such as endothelial cells), with subsequent improved cell migration and invasiveness, but no notable increase in proliferation 45 .…”
Section: Discussionmentioning
confidence: 95%
“…Heparanase overexpression in gastric cancer has been correlated with tumour invasion and metastasis 55–57. In contrast, silencing of heparanase expression blocked the growth, invasion and metastasis of gastric cancer cells 58 59…”
Section: Discussionmentioning
confidence: 96%
“…revealed that heparanase involved in the tumor invasion and metastasis of gastric cancer in vivo (20). Conversely, stable knockdown of heparanase expression can efficiently inhibit the invasiveness, metastasis and angiogenesis of human gastric cancer cells (25). Considering the results from our present study along with those of the studies mentioned before, we consider that heparanase expression might play an important role in inducing a poor outcome in patients with gastric cancer by promoting invasive and metastatic activities of gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%